2021
DOI: 10.1109/access.2021.3053547
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Answer Set Programming Encoding of Multi-Agent Pathfinding

Abstract: Multi-agent pathfinding (MAPF) is the problem of finding k non-colliding paths connecting k given initial positions with k given goal positions on a given map. In its sum-of-costs variant, the total number of moves and wait actions performed by agents before they definitely reach the goal is minimized. Not surprisingly, since MAPF is combinatorial, a number of compilations to Boolean Satisfiability (SAT) and Answer Set Programming (ASP) exist. In this paper, we describe in detail the first family of compilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…While the edge conflict can be defined by (a i , u, t) → (a i , v, t + 1), where agent a i tries to go to vertex v ∈ V from u ∈ V between time-steps t and t + 1. At the same time-step t, another agent a j tries to go to vertex u ∈ V from v ∈ V incurring head-to-head conflict in t + 1; that is, (a j , v, t) → (a j , u, t + 1) [39]- [41].…”
Section: A Multi-agent Path Findingmentioning
confidence: 99%
“…While the edge conflict can be defined by (a i , u, t) → (a i , v, t + 1), where agent a i tries to go to vertex v ∈ V from u ∈ V between time-steps t and t + 1. At the same time-step t, another agent a j tries to go to vertex u ∈ V from v ∈ V incurring head-to-head conflict in t + 1; that is, (a j , v, t) → (a j , u, t + 1) [39]- [41].…”
Section: A Multi-agent Path Findingmentioning
confidence: 99%
“…While the former (e.g., Sharon, Stern, Felner, & Sturtevant, 2012;Felner, Li, Boyarski, Ma, Cohen, Kumar, & Koenig, 2018;Li, Felner, Boyarski, Ma, & Koenig, 2019a) can scale to large maps, they do not perform very well in relatively small, dense maps. Compilation-based techniques, instead, translate the MAPF instance to an instance of another problem, for example Boolean satisfiability (SAT) (e.g., Surynek, Felner, Stern, & Boyarski, 2016;Barták, Zhou, Stern, Boyarski, & Surynek, 2017;Barták & Svancara, 2019;Surynek, Stern, Boyarski, & Felner, 2022), answer set programming (ASP) (e.g., Erdem, Kisa, Öztok, & Schüller, 2013;Gebser, Obermeier, Otto, Schaub, Sabuncu, Nguyen, & Son, 2018;Nguyen, Obermeier, Son, Schaub, & Yeoh, 2017;Gómez, Hernández, & Baier, 2021), or Mixed-Integer Programming (MIP) (e.g., Barták et al, 2017). They do perform better than search-based solvers in dense, rather small maps, but do not scale to large maps.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of compilation-based approaches depends on a number of factors, including the base SAT/ASP/MIP solver, but also on the encoding used. Recently, Gómez et al (2021) showed that focusing on generating a smaller encoding, linear on the number of agents rather than quadratic, yielded significant benefits in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASP is already used in time-related solving in a lot of different contexts, from planning trains [2] to moving robots in wharehouse [25] [18]. There exist some dedicated tools like Telingo [6] that are used for planning.…”
Section: Introductionmentioning
confidence: 99%